Isolation and characterization of transposable elements in chiropteran genomes - Castro, Francisca Manuela Teixeira Fernandes de (2024)
Long before the revolution of sequencing projects, it was well-known that genomes are not exclusively composed of single-copy sequences. However, for a long time, the repetitive portion of genomes was viewed as "junk DNA", without any biological function. Nonetheless, the advancements of scientific research have made possible to understand that the impact of the repetitive portion, and especially of transposable elements (TEs), extends far beyond their existence in genomes, being involved in the remodelling of genomic architecture and regulation of gene expression, among other functions. The order Chiroptera comprises around 20% of extant mammals and is characterised by a high variety of species, resulting from its great morphological and karyotypical diversity. Furthermore, chiropterans have peculiar traits that make them particularly interesting from an evolutionary point of view, including an extensive and diverse repertoire of TEs. The LINE-1 family is currently recognised as the most abundant class of TEs in mammalian genomes, similarly to SINEs, which also have a preponderant presence in these genomes. Although their presence is less pronounced, Helitrons have already been found in bat genomes, with an apparently restricted distribution to the Vespertilionidae family. In the present work, three families of TEs – L1, Ves (retrotransposons) and Hel-1 (transposon) – were isolated and characterised molecularly and cytogenetically in the genomes of three chiropteran species from Mainland Portugal – Myotis escalerai (MES), Myotis daubentonii (MDA) (Vespertilionidae), and Rhinolophus euryale (REU) (Rhinolophidae). To this end, a multidisciplinary approach was outlined, in which the physical and in silico mapping of the isolated TEs were conducted for the first time. Concurrently, the karyotype of REU was also organised for the first time in the course of this dissertation. The results obtained revealed that, contrarily to previous evidence, Hel-1 and Ves are not exclusive to vespertilionids, having been detected for the first time in a species from another family, the Rhinolophus studied in this work. In addition, the physical mapping revealed a species-specific distribution pattern of TEs in the genomes of the analysed species, which suggests their potential involvement in the diversification of genomes and, consequently, in the evolution of species. The pericentromeric accumulation of L1 observed in MDA may be indicative of the association between TEs and satellite DNA sequences. On the other hand, the accumulation at subtelomeric regions and on the Y chromosome points to a possible role for TEs in the heterochromatisation and/or inactivation of certain genomic regions or may result from the action of selective processes towards the elimination of insertions that occur in gene- rich regions. Finally, TEs may also be involved in the regulation of gene expression, since most of the insertions analysed in this study are orientated in the sense of transcription.